Prayer in Judaism- Comparative religions (Journal of the College of Basic Education, 2025)
Through our previous presentation of prayer and its concept, we find that prayer is the means that all human beings have taken, through which they turn to the Creator, supplicating, beseeching, and hoping for His acceptance, and this has been the case since the creation began on Earth.The research came out with results that can be summarized as follows:-:1.Prayer is a foundation and an important pillar in every human being's life.2.The Jewish religion requires purification and cleansing, and requires ablution with water when praying, when eating, at every sacred religious celebration, and when reciting the texts of the Torah.3.The Jews took (Jerusalem) as their qiblah, and whoever lives in Jerusalem, his qiblah is the temple.4.Jews have three obligatory prayers and there are many prayers that they have added as their prayers have varied according to their desires. There are prayers of thanks, prayers on holidays, prayers for forgiveness of sins, and other prayers.5- Jews take one day a week to devote themselves to worship and rest, as Jews sanctify the Sabbath.